Solving Multi-Objective Transportation Problem to reduce Transportation cost and Time - sharma, Gaurav (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we study the multi-objective transportation problem for Procter & Gamble to reduce transportation cost and time of goods supply from one source to another source. To solve this problem we are using a new proposed algorithm which is different form to another existing method. This proposed method providing the support to decision makers for handling time oriented problems.